2013
DOI: 10.1177/0954407013485567
|View full text |Cite
|
Sign up to set email alerts
|

A review of current automotive battery technology and future prospects

Abstract: In this article, today’s battery technologies and future options are discussed. Batteries have been one of the main focuses of automotive development in the last years. Technologies that have been in use for a very long time, such as the lead–acid battery, are indispensable but need improvement. New technologies such as the lithium-ion battery are entering the market. Supercapacitors (also known as electrochemical double-layer capacitors) can be used for high-power requirements such as regenerative braking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(125 citation statements)
references
References 18 publications
0
107
0
3
Order By: Relevance
“…In spite the fact this solution is possible, less than 1% of conventional cars has alternate solution [16]. In this way an observation from [2] has been confirmed.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In spite the fact this solution is possible, less than 1% of conventional cars has alternate solution [16]. In this way an observation from [2] has been confirmed.…”
Section: Introductionmentioning
confidence: 70%
“…al. have concluded that Lead-acid batteries are indispensable energy storage for conventional cars; however this type of batteries have to be improved [2]. First option is to use more advanced materials for electrodes in frame of Leadacid technology [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Batteries are the governing part of the vehicle where their selection, size, outline, transfer, and reusing affect the quality, lifetime, and security of the vehicle. [1] Table 1 summarizes the performances of different types of Electric vehicles. Because of expanding greenhouse emanations and developing risk to resource security at present powering the transportation sector, there is an extreme weight on automakers to devise a new technology that can fulfill the changing needs of the economy.…”
Section: Currently Available Conceptmentioning
confidence: 99%
“…[1] Other options, for example, nickel-metal hydride and sodium nickel chloride batteries, confront similar issues as lead acid and nickel cadmium batteries which have lower energy density, power, and execution. Besides, the alternative nickel batteries may likewise have a more critical effect on nature, giving a disincentive for future improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation